Editorial (Cadernos de Sociomuseologia, 2020)
The Journal of Sociomuseology was created in 1993 to serve, in the first place, the educational project of the newly created Department of Museology at the Higher Institute of Mathematics and Management (ISMAG), which in 1998 would be transformed into the Lusophone University of Humanities and Technologies.In fact, at that time, there was no journals dedicated to Museology in Portugal. During these 27 years, we have always considered that the journal could and should be, tool for sharing the scientific production of our programmes. It was in this context that articles by professors, students and guest professors were published. However, the reorganization of the journal in 2013 to adopt the criteria that characterize an international scientific publication, an objective achieved through the positive evaluation of several indexers, came to condition the origin of the published texts, in order to favor the publications of authors integrated in other institutions. This has been done, in particular as a result of the good relationship with many Brazilian universities. The present volume of journal of Sociomuseology publishes a set of articles by PhD students, some of whom are professors in other institutions and students of the Master in Museology, as a way of evaluating the meaning of the ongoing  research, as well as the work in which they are involved in their professional activity as musicologists. This volume thus reflects, in a way, not only the theoretical framework that supports the preparation of theses and dissertations, but also the guidelines that preside over the work of our Department of Museology.